Floral and genetic divergence across environmental gradients is moderated by inter-population gene flow in Platanthera dilatata (Orchidaceae) - Wallace, Lisa E.; Bowles, Marlin L. (Frontiers in Ecology and Evolution, 2023)
Understanding how natural selection acts on intraspecific variation to bring about phenotypic shifts is critical to understanding evolutionary diversification. Orchidaceae is well-known for pollinator-mediated selection of floral phenotypes, but its effectiveness at small spatial scales is less understood, making the geographic scale at which intraspecific floral variation is examined important to evaluating the reasons behind intraspecific phenotypic shifts. In this study, we quantified variation of two flower phenotypes of the orchid Platanthera dilatata across 26 populations in coastal Southeast Alaska and compared this to environmental and genetic variation at microsatellite loci. We sought to determine 1) if flower morphological variation is geographically structured, 2) the extent of genetic divergence between the phenotypes, 3) the scale at which inter-population gene flow occurs, and 4) the relative importance of geographic distance and abiotic factors on population genetic structure. The two morphological groups separate based on lip and spur length and are restricted to different habitats. Small flowered forms occur in muskeg bogs, whereas large-flowered forms occur across an edaphic gradient in fens and meadows, and rarely at high elevations where muskeg transitions to alpine habitat. Genetic analyses largely supported the morphological clusters, except for four small flowered populations that were genetically indistinguishable from large flowered populations. Most populations exhibited admixture, indicating that reproductive isolation is not complete between flower forms. Pollinators may partition phenotypes but also facilitate gene flow. Short-tongued Noctuidae moths pollinate both phenotypes, but longer tongued hawkmoths were only observed pollinating the large-flowered phenotype, which may strengthen phenotypic divergence. Nevertheless, pollinator movement between habitats could have lasting effects on neutral genetic variation. Given strong genetic divergence between phenotypic groups, they may have survived in distinct Pleistocene refugia. This may also impact genetic structure we observed as isolation by distance and environment were detected. At a smaller spatial scale, population genetic structure is only associated with environmental distance, likely due to extensive seed and pollinator movement. While this study corroborates previous findings of genetic and phenotypic divergence in P. dilatata, the scale of examination provided greater understanding of the factors that may underlie these divergences and taxonomic boundaries among its varieties.